Server to Mobile Device Communication: A Case Study - Anacleto, Ricardo (2015)
Develop a client-server application for a mobile environment can bring many challenges because of the mobile devices limitations. So, in this paper is discussed what can be the more reliable way to exchange information between a server and an Android mobile application, since it is important for users to have an application that really works in a responsive way and preferably without any errors. In this discussion two data transfer protocols (Socket and HTTP) and three serialization data formats (XML, JSON and Protocol Buffers) were tested using some metrics to evaluate which is the most practical and fast to use.